Gambaran Psychological Well-Being pada Petugas Lapangan Laki-Laki di BPBD Kota Surakarta - Andressia Yeiza Putri; Dhian Riskiana Putri; Sri Ernawati (Pusat Riset dan Inovasi Nasional, 2026)
The Regional Disaster Management Agency (BPBD) is tasked with disaster management activities in the form of preparedness, namely steps that enable governments, organizations, communities, and individuals to respond to disaster conditions quickly and appropriately. Preparedness efforts also aim to determine the use of resources needed to respond effectively in disaster situations when a disaster occurs and know how to use them. This study aims to analyze the psychological well-being of male field officers at the Surakarta City BPBD. This is revealed through descriptive qualitative methods. Data were collected through observation, interviews, and documentation. Then the data were analyzed using thematic analysis. The results of the study indicate that the majority of field officers have good psychological well-being, characterized by six aspects, namely self-acceptance, positive relationships with others, independence, environmental mastery, life goals, and personal growth. Field officers can manage themselves and negative emotions, have empathy, and dare to make decisions and take responsibility. Field officers also have good environmental mastery, are able to organize tasks and resources. They have meaning in life, especially through humanitarian contributions and use failure as a driver or motivation to continue learning and developing. This psychological well-being forms the basis of their mental resilience in carrying out humanitarian duties.